Digitalization of the buyer-seller relationship in the steel industry - Salo, Jari; Tan, Teck Ming; Makkonen, Hannu (Emerald, 2020)
Purpose The purpose of this research is to cast light on the nature of the digitalization process that occurs when digital technologies are adopted in buyer–seller relationships. Design/methodology/approach The study features a case study from the steel processing industry. Findings The present research builds on and extends the interaction approach to the context of buyer–seller relationship digitalization process. The study explicates the interrelated elements of digital infrastructure, digital communication, and degree of digitalization of the buyer-seller relationship. Research limitations/implications The study aims at theoretical generalization and thus produces conceptual understanding that is to some extent applicable to various contexts. The generalization of the empirical insights to other process-focused industries is to some extent possible. However, further research in versatile empirical contexts is needed to validate the results. Practical implications For managers, the study presents a success case of digital technologies use for improving a buyer–seller relationship. Originality/value The originality of the present research is in the way it depicts how a buyer–seller relationship is gradually digitalized in successive digital technology adoptions, that is, a virtuous cycle of digitalization, that creates and alters the digital infrastructure and digital communication processes between the buyer and the seller resulting in different outcomes (degrees of digitalization in the buyer–seller relationship).
Keywords: Business relationships; Buyer-seller relationships; case studies; Communication technologies; Digital tools; Information technology; digital technology; steel industry; case study; fi=Markkinointi|en=Marketing|